南極昭和基地での中層・超高層大気観測の新展開 - 中村, 卓司; 佐藤, 薫; 堤, 雅基; 山内, 恭; 佐藤, 亨; 冨川, 喜弘; 西村, 耕司; 江尻, 省; 阿保, 真; 津田, 卓雄; 川原, 琢也; 鈴木, 秀彦; et al. (2013)
In the VIIIth term JARE (Japan Antarctic Research Expedition) one of the prioritized projects was on ‘the global environmental change revealed through the Antarctic middle and upper atmosphere’. The major activity of this project is to profile the middle and upper atmosphere over Syowa station, and new powerful instduments such as PANSY (Program of ANtarctic Syowa MST/IS), a Rayleigh/Raman lidar, a millimeter-wave spectrometer have been installed and started operation. In the first three years in 2010-13, fruitful results have been obtained. On the other hand, the importance of vertical and latitudinal/hemispheric counplings has been understood more widely and the understanding of ‘whole atmosphere’ from the ground to upper atmosphere has b ecome out target, not only as a pure scientific interest but also from the point of view of prediction of near future and climate change prediction. Thus, we propose further extention of the observation of the lower, middle and upper atmosphere over Syowa station, utilizing the powerful instrument of PANSY radar, and other instruments, collaborating with satellite observations, network observations and new modelings. 第4回極域科学シンポジウム 特別セッション：[S] 南極研究の将来展望―第Ⅸ期6か年計画策定に向けて 11月14日（木） 国立極地研究所 ２階大会議室 conference object